Recent African strains of Zika virus display higher transmissibility and fetal pathogenicity than Asian strains - Fabien Aubry (Nature Portfolio, 2021)
Here, the authors compare seven low passage Zika virus (ZIKV) strains representing the recently circulating viral genetic diversity of African and Asian strains and find that African ZIKV strains have higher transmissibility in mosquitoes and higher lethality in both adult and fetal mice.